Modern literatures in Spain - Labanyi, Jo; Buffery, Helena; Delgado, Luisa Elena; Hooper, Kirsty; Olaziregi, Mari Jose (Cambridge Polity Press, 2023)
Jo Labanyi and Luisa Elena Delgado provide the first cultural history of modern literatures in Spain. With contributors Helena Buffery, Kirsty Hooper, and Mari Jose Olaziregi, they showcase the country's cultural richness and complexity by working across its four major literary cultures - Castilian, Catalan, Galician, and Basque - from the eighteenth century to the present. Engaging critically with the concept of the "national", Modern Literatures in Spain traces the uneven institutionalization of Spain's diverse literatures in a context of Castilian literary hegemony, as well as examining diasporic and exile writing . The thematically organized chapters explore literary constructions of subjectivity, gender, and sexuality; urban and rural imaginaries; intersections between high and popular culture; and the formation of a public sphere. Throughout, readings are attentive to the multiple ways in which literature serves as a barometer of cultural responses to historical change. An introduction to major cultural debates as well as an original analysis of key texts, this book is essential reading for students and scholars with an interest in the literatures and cultures of Spain"--Back cover.
Modernity and the singular nation (1700-1840s) -- From sensibility to desire: the contruction of the modern subject (1730s-1840s) -- The rise of the public sphere and the professionalization of the writer (1730s-1890s) -- Countering Castilian: from retrenchment to the Renaissance of peripheral national literatures (1710s-1890s) -- The uses of the past: writing the nation (1760s-1890s) -- Popular culture: exclusion and appropriation (1760s-1930s) -- Urban modernity and the provincial: changing concepts of time and space (1830s-1930s) -- The nation called into question (1890s-1920s) -- Writers and political commitment (1930s-1960s) -- Spain beyond Spain: exile and diaspora (1939-1980s) -- Catalan, Galician, and Basque literatures: recovery and institutionalization (1960s-1990s) -- Rewriting gender and sexuality (1970s-2020) -- Memory and forgetting (1970s-2020) -- Normalization, crisis, and the search for new paradigms (1975-2021).
includes bibliographical references (pages 293-316) and index.
Keywords: Basque literature -- History and criticism; Catalan literature -- History and criticism; Galician literature -- History and criticism; Spanish literature -- History and criticism